A prospective cohort study of injury in amateur and professional boxing. Issue 8 (28th June 2006) - Zazryn, T; Cameron, P; McCrory, P
Abstract : Background: There is concern over the potential for a high incidence of injury in boxing. This is despite a lack of prospective data evaluating the risk for modern day participants. Updated, reliable data with a focus on potential exposure to injury for both amateur and, especially, professional boxers is required. Aim: To determine the epidemiology of injury and exposure of amateur and professional boxers in Victoria, Australia. Methods: A prospective cohort study with one year follow up was carried out over 2004–2005. Thirty three amateur and 14 active professional boxers registered with either Boxing Victoria Inc (amateurs) or the Professional Boxing and Combat Sports Board of Victoria (professionals) volunteered. Exposure at training and competition was measured, and any injuries sustained during this participation were recorded. Results: Twenty one injuries were sustained by the cohort during the follow up period. Most were to the head region (71%; 95% confidence interval −3.7 to 89.4), with concussion being the most common (33%). An overall injury rate of 2.0 injuries per 1000 hours of boxing was calculated. Conclusion: The high exposure experienced by the boxers (as a result of considerable training time) indicated that boxing has acute injury rates comparable to, and often lower than, those found in other contact and non-contact sports. Further, acute injuries during training appear to be less common and severe than those sustained in bouts.